(untitled) (Training and Practice : Journal of Educational Sciences, 2022)
Museums are ideal venues for engagement in education for sustainability. Collections can allow students to study and interpret connections between the presentation of inanimate natural values and the description of living natural values. In museums, the intensity of environmental education for students can be increased. The study focuses on finding some common points between environmental education and the educational activities of museum pedagogy. It tries to provide a literature review and formulates empirical research goals.